Pengaruh Metode Storytelling terhadap Kemampuan Public Speaking Mahasiswa Program Studi Ilmu Komunikasi di Kota Pekanbaru - Fatmawati Moekahar; Yudi Daherman (Jurnal Riset Komunikasi (JURKOM), 2021)
The implementation of public speaking becomes the most important part when appearing to provide information to the audience, so that the development of knowledge about storytelling has an influence in the learning process of students' public speaking lectures. Considering the process that students go through in practice which will be carried out simultaneously, various methods in practice have been implemented, and one of them students can develop themselves by using the storytelling method. This study aims to find out the effect of the storytelling method on the public speaking ability of students of the Communication Science study program in the city of Pekanbaru. This study uses the design of the Explanatory Survey Method. The results showed that the effect of storytelling on the students' public speaking skills was in the high category. This means that the more often students practice public speaking using the storytelling method, it will have an impact on their public speaking practice. Through the significance test of the storytelling method and the students' public speaking skills, there was a significant relationship. Communication Studies students will face the challenges of the current modernization era by developing digital storytelling methods. Modern society is now contaminated with all digital activities. So that the appearance of public speaking is also required to join in the practice.